Neck of Femur Fracture in a Patient with a Chronic Osteomyelitis of the Ipsilateral Foot - Anne-Carolin Döring; Anne J. H. Vochteloo; Kees van Doorn; Rianne M. H. A. Huis in ’t Veld; Anil Peters (Case Reports in Orthopedics)
This case report describes a successful two-stage treatment in a 75-year-old male with a displaced neck of femur fracture, also suffering from an active chronic osteomyelitis of the ipsilateral calcaneus. In our case, a below-knee amputation was performed first, followed by total hip arthroplasty two weeks later. At 15-month follow-up, full recovery of the prefracture level of activities of daily living without significant impairment was obtained. Only a few cases of total hip arthroplasty in amputees have been published, but the indication for surgery was mainly traumatic or advanced osteoarthritis. Treating patients with this type of comorbidities is challenging; therapeutic dilemmas can be major. The management in cases like these requires a thorough evaluation and a clear surgical and medical treatment plan, preferably conducted by a multidisciplinary orthogeriatric team.